1989
DOI: 10.1002/ejsp.2420190605
|View full text |Cite
|
Sign up to set email alerts
|

Social representations and memory: The case of AIDS

Abstract: In this study evidence is given on the mechanisms subjects use to guarantee the stability of their social representations. A n initial interview was held in which subjects REPRESENTATIONS AND MEMORYThe objective of this study is to analyze the mechanisms involved in keeping a social representation stable. Most studies in social representations are static analyses of already established representations and their influence as an independent variable on a particular phenomenon of interest. In this study we aim to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
3

Year Published

1991
1991
2000
2000

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 16 publications
1
11
0
3
Order By: Relevance
“…Why so few respondents had an accurate understanding of multiculturalism is an interesting issue. Moscovici (1973Moscovici ( , 1987 has frequently discussed the way that social representations are involved in the transformation of knowledge, and studies have shown that people select information for processing that is congruent with preexisting representations, and distort the recall of contradictory information (Echabe & Paez-Rovira, 1989). The results here appear to be another example of this phenomenon-of information being manipulated in order to retain a nonthreatening social representation of multiculturalism.…”
Section: Discussionmentioning
confidence: 57%
“…Why so few respondents had an accurate understanding of multiculturalism is an interesting issue. Moscovici (1973Moscovici ( , 1987 has frequently discussed the way that social representations are involved in the transformation of knowledge, and studies have shown that people select information for processing that is congruent with preexisting representations, and distort the recall of contradictory information (Echabe & Paez-Rovira, 1989). The results here appear to be another example of this phenomenon-of information being manipulated in order to retain a nonthreatening social representation of multiculturalism.…”
Section: Discussionmentioning
confidence: 57%
“…These search (statistically) for groups of similar ratings or answers. So Group A might show common attitudes, beliefs, and attributions, which are consistent and coherent within Group A, while Group B shows another typical pattern which is consistent and coherent within Group B but not with those of Group A (e.g., Echabe & Rovira, 1989;Hewstone, Jaspars & Lalljee, 1982). This is important work, and I am not suggesting that it should stop.…”
Section: Social Representation Theorymentioning
confidence: 91%
“…Category-inconsistent information is more likely to be discounted when information is either complex or ambiguous (Echabe & Rovira, 1989;Lord, Ross, & Lepper, 1979). Therefore, the discounting hypothesis predicts that subjects will vote as a function of party line in Study I , when they are presented with candidates whose policy positions are predominantly but not completely inconsistent with their party label.…”
Section: The Discounting Hvpothesismentioning
confidence: 95%